PENCAPAIAN PEDAGOGICAL CONTENT KNOWLEDGE MELALUI PEMBELAJARAN MATEMATIKA - Ningsih, Sri Yunita; Siagian, Muhammad Daut (Mahesa Research Center, 2020)
Pedagogical content knowledge is a combination of understanding of teaching material (content knowledge) and understanding how to educate (pedagogical knowledge) that needs to be possessed by a teacher. The purpose of this study was to determine the pedagogical content knowledge concept, the achievement of pedagogical content knowledge for prospective teacher students, and to determine the role of prospective mathematics teacher students towards pedagogical content knowledge. A teacher in carrying out his professional assignments must have the competence that is always maintained. Because of this, competency development is an important requirement to ensure that the quality of learning in the classroom adjusts to the development and demands of the times. Always maintained competence also ensures that the implementation of education is consistent in achieving educational goals. There are ten pedagogical content knowledge criteria that must be possessed by prospective teacher students before conducting the practice in the field. Prospective teacher students must also be able to implement learning, knowledge of ways to represent and explain the material to make the material understandable to others.